2017
DOI: 10.1016/j.jss.2017.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Violent reinjury risk assessment instrument (VRRAI) for hospital-based violence intervention programs

Abstract: Background Violent injury is the second most common cause of death among 15–24 year-olds in the US. Up to 58% of violently injured youth return to the hospital with a second violent injury. Hospital-based violence intervention programs (HVIP) have been shown to reduce injury recidivism through intensive case management. However, no validated guidelines for risk assessment strategies in the HVIP setting have been reported. We aimed to use qualitative methods to investigate the key components of risk assessments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…HVIPs have been shown to dramatically reduce the risk of reinjury, with one study citing a fourfold reduction after implementation of changes to screen patients for reinjury risk and provide resources for mentorship, mental health services, and risk factor modifications. [22][23][24] In addition, cost-effectiveness analysis of HVIPs have demonstrated clear benefits in reducing patient and hospital costs, largely due to reduced recidivism rates. 25,26 There are several limitations present in this study.…”
Section: Discussionmentioning
confidence: 99%
“…HVIPs have been shown to dramatically reduce the risk of reinjury, with one study citing a fourfold reduction after implementation of changes to screen patients for reinjury risk and provide resources for mentorship, mental health services, and risk factor modifications. [22][23][24] In addition, cost-effectiveness analysis of HVIPs have demonstrated clear benefits in reducing patient and hospital costs, largely due to reduced recidivism rates. 25,26 There are several limitations present in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Major goals of such programming are to increase patient education and engagement, to promote recovery and well-being in the community, and to limit recidivism in this high-risk group. Although new to our institution, other hospitals around the country have investigated the impact of similar violence intervention programs 30–34. These programs have noted a number of benefits including reduced recidivism, cost savings, and transformed attitudes about violence and shame 32–34.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Losing control of emotions, including:"being drunk", "having a diagnosed or suspected mental disorder". Previously, Bataille found alcohol abuse is one of the most common triggers of WPV in ED [34]; a lot of other research has similarly found drunkenness and mental disorders are often associated with physical violence against healthcare providers [24,[35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%